Ecological Study on Zooplankton of Some Fresh Water Bodies of Kathmandu Valley With Reference to Water Quality - Vaidya, Sunil Ram; Yadav, Umakant Roy (Journal of Natural History Museum, 2009)
The present investigation was carried out in Bagmati river (Lotic water body), Taudah lake, Nag pokhari pond, Siddha pokhari pond and Godavari fish pond (Lentic water bodies) of the Kathmandu valley from May 2000 to April 2002. A monthly samples of water and zooplanktons were collected from those sites and analyzed for the entire twenty four months period. Only three groups of zooplankton viz: Rotifera, Cladocera and Copepoda were collected from the lotic and lentic water bodies. It was observed that Rotifers were found to be more diversified than Cladocerans and Copepods in all water bodies except in Nagpokhari. A total of seventy one species of zooplankton were recorded during that period. The lentic water bodies supported a higher species richness constituting seventy species whereas the lotic water bodies constituted only seven species of zooplankton. All investigated zooplanktons Rotifera, Cladodera and Copepoda were found contagiously distributed in all lentic water bodies. In the Bagmati river, Rotifers were recorded only in the upstream zone. Cladocerans predominated (74 %) in the upstream, Copepods predominated (70 %) in the mid-stream and again Cladocerans predominated (60 %) in the down-stream of the river. Among the investigated water bodies, the species richness was found higher in Godavari fish pond (36 species) than Taudah lake (35 species), Siddha pokhari (34 species) and Nag pokhari (26 species).The water quality of the investigated waterbodies were found to be deteriorated due to discharge of untreated effluents,solid wastes and poor conservation practices. Journal of Natural History Museum Vol. 23, 2008 Page 1-11